Single-cell transcriptomes of the human skin reveal age-related loss of fibroblast priming - Solé-Boldo, Llorenç; Raddatz, Günter; Schütz, Sabrina; Mallm, Jan-Philipp; Rippe, Karsten; Lonsdorf, Anke Susanne; Rodriguez-Paredes, Manuel; Lyko, Frank (Communications biology, 2020)
Fibroblasts are an essential cell population for human skin architecture and function. While fibroblast heterogeneity is well established, this phenomenon has not been analyzed systematically yet. We have used single-cell RNA sequencing to analyze the transcriptomes of more than 5,000 fibroblasts from a sun-protected area in healthy human donors. Our results define four main subpopulations that can be spatially localized and show differential secretory, mesenchymal and pro-inflammatory functional annotations. Importantly, we found that this fibroblast 'priming' becomes reduced with age. We also show that aging causes a substantial reduction in the predicted interactions between dermal fibroblasts and other skin cells, including undifferentiated keratinocytes at the dermal-epidermal junction. Our work thus provides evidence for a functional specialization of human dermal fibroblasts and identifies the partial loss of cellular identity as an important age-related change in the human dermis. These findings have important implications for understanding human skin aging and its associated phenotypes. Sole-Boldo et al characterise dermal fibroblasts in human skin not exposed to sunlight by single-cell RNA sequencing. They identify fibroblast subpopulations and see that aging reduces their identity and predicted interactions with other skin cells, providing insights into age-related changes in skin.